Analysis of Distributed File System Replication Using the NDLC Method with Hyper-V Virtual Simulation Machine - Sumirat, Ucu; Setiawan, Antonius; Wilyanti, Sinka; Al-Hakim, Rosyid (CV. Media Digital Publikasi Indonesia, 2023)
The need to access file sharing easily on an organization's computer network was increased. Users didn't have to worry about the number of file server addresses that can be accessed and are made with only one access address to use file sharing. The availability of data on the network to file storage availability in an organization was also essential. Data would be permanently lost, following a reason including hardware failure, or even accidentally deleted. It was important to ensure that there was a copy of the data. Achieving good data availability requires a system strategy built in the organization's data center. This research used Distributed File System Replication (DFSR) based on active directory domain services with Windows Server. The research method used NDLC (Network Diagram Life Cycle) method. This research was conducted through analysis with the Hyper-V virtual simulation machine. The results of the research with this simulation are that the Distributed File System (DFS) makes it easy for users to access file shares on several file server nodes using only one URL address. DFSR makes it easy for users to clone files automatically on multiple nodes file servers at other locations. DFSR, with its Share and Publish features, provide good data availability. If one of the file server nodes experiences an interruption, the file server nodes at another location would be taken over to provide the data. This system makes it easy for administrators to manage file servers